Estimation of distance between two 802.11p transceivers based on RSSI - Mong, Aaron Feng Cheng (2015)
In the modern world, wireless communications has impacted our daily life. The use of such equipment has relatively made many things convenient and more easily accessible. The increasing rate at which cars are being used these days has been rapidly growing and much research into vehicular wireless communications have yield technologies such as the GPS (Global Positioning System) to aid vehicles on the road. Mobile vehicles has been growing to be more reliant on GPS to navigate to a destination as it is more efficient to get live data and to know the exact route you have to take instead of looking at the map at every stop to determine where you might be. This has reduced the time consumed to reach a specific destination and people value the amount of time they can conserve. With this in mind, we decided to explore vehicle-to-vehicle (V2V) communications and applications that can be used in daily life. One such method is to use localization methods to compute a car’s relative distance from another car if in case GPS is unreachable. For this project, we will investigate the use of the COHDA MK4 Units for V2V communications and car-to-car measurements that can improve localization for cars. GPS are generally not suitable to be established indoors such as underground, tunnels and etc. This is because the microwaves would be attenuated and scattered by roofs, walls and other objects. In conclusion, we will make use of the COHDA MK4 to incorporate algorithms that estimates the distance from another vehicle based on RSSI. This would further augment the GPS system for a better coverage for indoor positioning estimate that would enable vehicles to still know their coordinates even if GPS signal is lost i.e. When vehicles are in tunnels/underground or in heavily congested area where GPS data traffic is heavily impeded and thus users are able to make use of this augmentation method to find out the coordinates of where they are on the map.